Physicochemical characterization of polyimide (PI) / p-aramid: New functional and safe materials with improved heat resistance by a simple coating of polyimide on the surface of p-aramid - Lee, Jaewoong; Kim, Sam Soo; Kang, Dakyung; Roh, Changhyun; Kang, Chankyu (Progress in organic coatings, 2019)
[Display omitted] •PI/ p-aramid composite yarns formed through the stepwise coating to improve heat resistance.•The pyrolysis temperature of PI / p-aramid yarn after heat treatment at 350 °C was higher than that of existing p-aramid yarn.•The imidization of PI is affected by temperature, heat treatment time, and catalyst usage.•The PI / p-aramid coated yarn improved tensile strength.•Long-term exposure to 250 °C is required to improve physical and chemical properties of the p-aramid yarn. With excellent heat resistance and chemical resistance, p-aramid is used in a variety of industrial applications. In this study, the polyimide (PI) precursor was coated on the surface of p-aramid yarn and studied the changes in heat resistance and physicochemical properties of composite PI / p-aramid yarns. Changes in peaks by imidization of PI using XRD and FT-IR, surface characteristics through SEM, and thermal properties analyzed by TMA and TG-DTA were measured. The degree of imidization of PI films were quantitatively investigated by FT-IR analysis. Through these analyzes, the following results were revealed: (1) the imidization of the PI was confirmed that the thermal imidization process at 350 °C was suitable; (2) the physical properties of the PI film were affected by the imidization temperature, the heat treatment time and the amount of the catalyst; and (3) the tensile strength of PI / p-aramid coated yarn was higher than that of conventional uncoated p-aramid yarn at 200–350 °C. Therefore, PI/ p-aramid composite yarns formed through the stepwise coating were found to improve thermal properties including initial thermal degradation temperature compared to no PI coating.